Geoteknik jasa Jurusan PTSP Fakultas Teknik UNM - Taufiq Natsir (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
To support the efforts to develop an entrepreneurial culture at Makassar State University (UNM vision), it is necessary to encourage and improve the empowerment of laboratories in the Department of Civil Engineering Education and Planning of the Faculty of Engineering which consists of 3 (three) workshops (wood / furniture, concrete stone, plumbing) and consists from 5 (five) laboratories (surveying and mapping, material testing, soil testing, highways, hydraulics, and 1 (one) studio image (digital and manual). The existence of equipment in this laboratory, workshop and study picture, if empowered believed to be able to provide a large income especially PPUPIK from DRPM Kemenristek dikti then it can be tested through : Geotechnical Product Service PTSP Departement Faculty of Engineering Makassar State University. The long-term goal of this activity is to make the Laboratory of Civil Engineering Education and Planning a center for Geotechnical services which includes Mapping Surveys, Soil Mechanics, Materials and Materials Tests and Transportation Engineering. The methods used to achieve the above objectives are: 1. Doing business promotion through advertisements (newspapers, radio, websites, pamphlets, banners, benner, brochures); 2. Establish cooperation and partnerships (government agencies / institutions / institutions / companies, schools / colleges / tutoring, associations / individuals) both government and private..